Vol 2 No 1 EKONOMI KERAKYATAN DALAM PERSPEKTIF EKONOMI SYARI'AH: PERANAN KOPERASI DALAM MENINGKATKAN EKONOMI KERAKYATAN - nidhom, Misbahun (PRODI ES SEKOLAH TINGGI ISLAM KENDAL, 2024)
Cooperatives as business entities that are owned and utilized by members, are confirmed in Law number 25 of 1992. The boundaries of cooperatives in this law have a stricter and clearer meaning than the old boundaries, in Law no. 12 of 1967, which allowed the creation of dual thinking about cooperatives. Law number 25 of 1992 accommodates changes at the instrumental level, such as the regulation of